Faktor-Faktor Yang Berhubungan Dengan Kualitas Hidup Lansia Desa Paya Dapur Kecamatan Kluet Timur Kabupaten Aceh Selatan Tahun 2021 - Masliati, Maidar, Agustina (Journal of Health and Medical Science, 2022)
The aging process in the elderly causes a decrease in both physical, psychosocial, functional and cognitive status which will have an impact on aspects of life both socially, economically, especially health which will determine the quality of life of the elderly themselves. Quality of life is the existence of hopes and goals that individuals have to have a better life, a good quality of life is also needed to protect the elderly from various problems that are often experienced by the elderly.Data from the East Kluet Health Center shows that the number of elderly residents of Paya Dapur is 159 (9.3%) of the total population and only 20 (12.5%) use health facilities. The purpose of the study was to find out what factors were related to the quality of life in the elderly in Paya Dapur Village, East Kluet District, South Aceh Regency in 2021. This research was conducted using descriptive analytic method with a cross- sectional approach. The population in this study were elderly people aged 60 years and over in Paya Dapur Village, East Kluet District as many as 95 elderly from the entire population. Data collection was carried out for 9 days from 08 to 16 August 2021 using a questionnaire through interviews. Data analysis used Chi Square test with SPSS computer program. The results showed that there was no relationship between age (p-Value = 0.389), gender (p-Value = 0.384), employment status (p-Value = 0.132), marital status (p-Value = 0.146), utilization of health facilities (p-Value = 0.734) and the quality of life of the elderly. And there is a relationship between education (p-Value = <.001) with the quality of life of the elderly in Paya Dapur Village, East Kluet District, South Aceh Regency in 2021. The conclusion is that education is related to the quality of life in the elderly, while age, gender, employment status, marital status, and utilization of health facilities are not related to the quality of life in the elderly. It is hoped that the East Kluet Health Center will continue to improve and support the elderly healthprogram, especially the elderly who have chronic diseases. So that it can help the elderly in preventing and overcoming psychosocial problems, improving health status and improving the quality of life of the elderly.